Historiographic Metafiction in Hilary Mantel's Bring Up the Bodies (2012) - BESSALEM ,Zahia; HOCINE,Aicha (University of Ammar Theledji -Laghouat, 2020)
The historical novel has developed over the twentieth century and most of postmodern authors have embraced historiographic metafiction in their literary historical works which have combined both elements of history and elements of fiction. The readers‟ inability to believe in historical novelists and how they extract truth from those postmodern historical novels remains a prominent issue of postmodern novels. The aim of this dissertation, then, was to portray how Hilary Mantel (1952) used historiographic metafiction in her sequel novel Bring up the Bodies (2012), to question the truth of historical inquiries that were mixed with imaginative details in the novel and to highlight the importance of the multiplicity of interpretations of the author/reader to form a new distinct meaning, as it aimed to demonstrate Mantel as a reliable and a faithful author. To achieve this aim, the historical, analytical and explanatory approaches were adopted. The research was structured in three chapters, in which it analysed the accordance of both the philosophy of postmodernism and the philosophy of history in relation to the postmodern historical fictional novel, and explained how historiographic metafiction presented accounts of the past. It, further, explored whether a historical novelist was a reliable author. It was argued, in this study, that the historical novelist presented truth according to different understandings and interpretations of the past records. As a result, Hilary Mantel‟s contribution to historiographic metafiction demonstrated her reliability and credibility as historical fictional author. From this point, historiographic metafiction plays a significant role in representing the past while stressing the significance of different understandings and interpretations of both the author and the reader